Interdecadal Trichodesmium variability in cold North Atlantic waters. Issue 11 (5th November 2016) - Rivero‐Calle, Sara; Del Castillo, Carlos E.; Gnanadesikan, Anand; Dezfuli, Amin; Zaitchik, Benjamin; Johns, David G.
Abstract: Studies of the nitrogen cycle in the ocean generally assume that the distribution of the marine diazotroph, Trichodesmium, is restricted to warm, tropical, and subtropical oligotrophic waters. Here we show evidence that Trichodesmium are widely distributed in the North Atlantic. We report an approximately fivefold increase during the 1980s and 1990s in Trichodesmium presence near the British Isles with respect to the average over the last 50 years. A potential explanation is an increase in the Saharan dust source starting in the 1980s, coupled with changes in North Atlantic winds that opened a pathway for dust transport. Results from a coarse‐resolution model in which winds vary but iron deposition is climatologically fixed suggest frequent nitrogen limitation in the region and reversals of the Portugal current, but it does not simulate the observed changes in Trichodesmium . Our results suggest that Trichodesmium may be capable of growth at temperatures below 20°C and challenge assumptions about their latitudinal distribution. Therefore, we need to reevaluate assumptions about the temperature limitations of Trichodesmium and the dinitrogen (N2 ) fixation capabilities of extratropical strains, which may have important implications for the global nitrogen budget. Key Points: Trichodesmium were found year‐round in North Atlantic high latitudes, as far as 65 degrees N and temperatures as low as 3 degrees C Increased dustiness, nitrogen limitation, and drift are discussed as possible drivers for Trichodesmium increases in the 1980‐1990s Trichodesmium growth and N2 fixation may not be limited to warm (sub)tropical waters